Prediction of Significant Coronary Artery Disease Through Advanced Echocardiography: Role of Non-invasive Myocardial Work - Sabatino, Jolanda; De Rosa, Salvatore; Leo, Isabella; Strangio, Antonio; Spaccarotella, Carmen; Polimeni, Alberto; Sorrentino, Sabato; Di Salvo, Giovanni; Indolfi, Ciro (Frontiers in Cardiovascular Medicine, 2021)
Background. Non-invasive prediction of critical coronary artery stenosis (CAST) in patients with coronary artery disease (CAD) is challenging. Strain parameters can often capture an impairment of regional longitudinal function; However, they are load dependent. A novel non-invasive method to estimate Myocardial Work (MW) has been recently proposed, showing a strong correlation with invasive work measurements. Our aim was to investigate the ability of non-invasive MW to predict the ischaemic risk area underlying a CAST. Methods and results. The study population comprises 80 individuals: 50 patients with CAST and 30 controls (CTRL). Echocardiography recordings were obtained before coronary angiography to measure global longitudinal strain (GLS), Myocardial Work Index (MWI), Myocardial Constructive Work (MCW), Myocardial Wasted work (MWW), Myocardial work efficiency (MWE). Global MWI (p=0.048), MWE (p<0.001) and MCW (p=0.048) at baseline were significantly reduced in patients with CAST compared to controls (p<0.05). Regional MWE within the myocardial segments underlying the CAST, but not LS, was significantly reduced compared to non-target segments (p<0.001). At ROC analysis, the diagnostic performance to predict CAST for regional MWE (AUC=0.920, p<0.001) was higher compared to both regional post-systolic shortening index (PSI) (AUC=0.600, p=0.129) and regional LS (AUC=0.546, p=0.469) Conclusions. Non-invasive estimation of MW work indices is able to predict a CAST before invasive angiography.